A preliminary studies on ethic of muslim entrepreneurs / Intan Liana Suhaime … [et al.] - Suhaime, Intan Liana; Jogeran, Jumaelya; Sehat, Nani Shuhada; Mad Saat, Rosfadzimi; Daud, Siti Rohana (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2017)
Quran stipulates: “and give measures and weight with (full) justice.” (The Quran 6: 152) and also “and give not short measure or weight.” (The Quran 11:84). This reminder signifies that there is always the tendency of committing fraud and irregularities in any business transactions, whether simple or complex which will result in prolong disputes between the parties involved. Entrepreneurs are individuals who actively form or lead their own businesses and nurture them for growth and prosperity. In this endeavor, entrepreneur cannot get away from the lure of high turnover, even if it results in customers becoming victims. Growing number of fraud cases either from online or offline business shows mishandling of information that is passed to the consumers. Consumers then were influx with deceived facts that may lead them in purchasing unneeded item(s). Hence, this study is to explore the awareness among Muslim entrepreneurs about Islamic entrepreneurship principles that they should conduct while operating their businesses.